The Private Hopes of American Fundamentalists and Evangelicals, 1925-1975 - Watt, David Harrington (Religion and American culture, 1991)
Much of the best recent scholarship on conservative Protestantism in the middle decades of this Century focuses on what is sometimes called the “mainstream” of interdenominational evangelicalism. Although this variety of evangelicalism was deeply influenced by and, indeed, in some respects the direct successor to the fundamentalist movement of the 1910's, 1920's, and 1930's, it did not begin to assume its present shape until the early 1940's. The formation of the National Association of Evangelicals in 1942 is a convenient symbol of the emergence of what we now think of as constituting the evangelical mainstream. Drafting a perfect definition of this mainstream is impossible; drafting a good working description of it is not. In the present context, “evangelical mainstream” simply refers to that network of born-again Christians associated with the Billy Graham Evangelistic Association, the National Association of Evangelicals, and Campus Crusade for Christ; with schools such as the Moody Bible Institute, Füller Seminary, and Wheaton College; with publishing firms like Eerdman's and Zondervan; and with magazines such as Christianity Today, Eternity, and Moody Monthly.